Pembuatan Ensiklopedia Cagar Budaya di Kota Sawahlunto Sumatera Barat - Asmarani, Dyah Roro Puspita; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
In this paper discussed about Making an encyclopedia of cultural heritage in the town of Sawahlunto. The purpose of this paper is to describe the process of creating the encyclopedia of cultural heritage in the West Sumatra town of Sawahlunto. The research methods used in this thesis paper writing is to use descriptive research methods and techniques of data collection was done through direct observation and interviews as well as libraries that use reading materials that are considered important.On the basis of discussion can be concluded stage of creation of Encyclopedia of cultural heritage in the town of Sawahlunto are as follows. First, the collection of data, conducted interviews with staff and observations related directly to the place of cultural heritage. Second, content design encyclopedia, before making a product, the author makes the draft form of the inside of the product that will be described in the form of a chart. Lastly, the manufacture of a product, based on the contents of the draft heritage encyclopedia, then the last step is the process of creating the encyclopedia of cultural heritage in the town of Sawahlunto West Sumatra Province as follows: (1) preface contains a couple of paragraphs that contain author credits to God Almighty, to parties who have been helping and giving support, the basis and purpose of prototype encyclopedias, hope, and accompanied with a , month, and year of the book made by the author. (2) the table of contents to find out what cultural heritage objects contained in the encyclopedia. (3) the content of the subject matter the book contains articles about cultural heritage objects that exist on the encyclopedia. (4) the index of the book is a list of important words or terms are arranged alphabetically in the backyard. (5) the front cover (cover) is a skin on the outside of the book that contains the title of the book, and is accompanied by some supporters of the image.Keywords: cultural, encyclopedia, heritage.